2019
DOI: 10.1128/jvi.00023-19
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening and Identification of Potent Broad-Spectrum Inhibitors of Coronaviruses

Abstract: Coronaviruses (CoVs) act as cross-species viruses and have the potential to spread rapidly into new host species and cause epidemic diseases. Despite the severe public health threat of severe acute respiratory syndrome coronavirus and Middle East respiratory syndrome CoV (MERS-CoV), there are currently no drugs available for their treatment; therefore, broad-spectrum inhibitors of emerging and endemic CoVs are urgently needed. To search for effective inhibitory agents, we performed high-throughput screening (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
309
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(324 citation statements)
references
References 67 publications
9
309
0
6
Order By: Relevance
“…Through in silico and biological processing, a series of small molecules, including those from natural compounds, have been screened and confirmed to directly inhibit these important proteins in SARS or Middle East respiratory syndrome (MERS) coronavirus [17][18][19][20][21][22][23]. The gene sequence of 2019-nCoV has been released, which suggests high similarities between the main proteins in this virus and those previously identified in SARS-Cov or MERS-Cov [24,25].…”
Section: Introductionmentioning
confidence: 93%
“…Through in silico and biological processing, a series of small molecules, including those from natural compounds, have been screened and confirmed to directly inhibit these important proteins in SARS or Middle East respiratory syndrome (MERS) coronavirus [17][18][19][20][21][22][23]. The gene sequence of 2019-nCoV has been released, which suggests high similarities between the main proteins in this virus and those previously identified in SARS-Cov or MERS-Cov [24,25].…”
Section: Introductionmentioning
confidence: 93%
“…Cell viability assays include MTT, MTS, resazurin or similar assays, mitochondrial membrane potential-dependent dyes-based assays, esterase cleaved dye-based assays, ATP-ADP assays, and assays that measure glycolytic flux and oxygen consumption. Other cell death assays include LDH enzyme leakage assays, membrane impermeable dye-based assays, and apoptosis assays, such as Annexin V, TUNEL, and caspase assays (Shen et al, 2019). For example, the Cell Titer Glo (CTG) assay quantifies ATP, an indicator of metabolically active living cells, whereas Cell Tox Green assay uses fluorescent asymmetric cyanine dye that stains the DNA of dead cells (Bosl et al, 2019;Bulanova et al, 2017;Ianevski et al, 2018;Muller et al, 2014).…”
Section: Discovery Of Novel Bsaa Activities In Immortalized Cell Cultmentioning
confidence: 99%
“…Given that emetine also inhibits ZIKV, EBOV, RABV, CMV, HCoV-OC43 and HIV-1 infections (Chaves Valadao et al, 2015;MacGibeny et al, 2018;Mukhopadhyay et al, 2016;Shen et al, 2019;Yang et al, 2018), and that it is an FDA-approved antiprotozoal drug, it may represent a promising safe-in-man BSAA candidate. (Carter and Shieh, 2015).…”
Section: Discovery Of Novel Bsaa Activities In Immortalized Cell Cultmentioning
confidence: 99%
See 1 more Smart Citation
“…The SARS-CoV-2 virus shared 79.5% genetic homology to the SARS-CoV and both are descendants of bat coronaviruses within the Betacoronavirus genus . Antiviral compounds previously reported to show effect against SARS-CoV or other coronaviruses may be effective against SARS-CoV-2 (Chu et al, 2004;de Wilde et al, 2014;Dyall et al, 2014;Shen et al, 2019;Cao et al, 2015). In addition, remdesivir (GS-5734), a prodrug of adenosine analog with a broad-spectrum antiviral activity against filoviruses, paramyxoviruses, and coronaviruses (Brown et al, 2019;Sheahan et al, 2017;de Wit et al, 2020), was recently confirmed to inhibit 2019-nCoV in vitro .…”
mentioning
confidence: 96%